Placement Design of Changeable Message Signs on Curved Roadways - Zhongren Wang, Ph.D. P.E. T.E.; Hiep Nguyen; Chiu Liu, P.E. T.E., PTOE, PhD, F. ASCE (International Journal of Transportation Science and Technology, 2015)
This paper presented a fundamental framework for Changeable Message Sign (CMS) placement design along roadways with horizontal curves. This analytical framework determines the available distance for motorists to read and react to CMS messages based on CMS character height, driver's cone of vision, CMS pixel's cone of legibility, roadway horizontal curve radius, and CMS lateral and vertical placement. Sample design charts were developed to illustrate how the analytical framework may facilitate CMS placement design.